2020
DOI: 10.1111/jan.14333
|View full text |Cite
|
Sign up to set email alerts
|

A web‐based therapeutic patient education intervention for pain and sleep for women with fibromyalgia: A sequential exploratory mixed‐methods research protocol

Abstract: Aims:To evaluate cognitive and behavioural factors related to pain and poor sleep quality in women diagnosed with fibromyalgia and to develop and test the effects of a web-based therapeutic education intervention on pain intensity, pain catastrophizing, chronic pain self-efficacy, sleep quality, dysfunctional beliefs and attitudes about sleep and quality of life and health status related to fibromyalgia. Design:The project will employ a sequential exploratory mixed methods research design.Methods: For the qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 71 publications
1
17
0
1
Order By: Relevance
“…Higher scores indicated greater fatigue severity. Previous studies support the validity and reliability of this questionnaire [7].…”
Section: Instrumentsupporting
confidence: 69%
See 1 more Smart Citation
“…Higher scores indicated greater fatigue severity. Previous studies support the validity and reliability of this questionnaire [7].…”
Section: Instrumentsupporting
confidence: 69%
“…The main symptoms reported by patients include musculoskeletal pain without external stimuli, specific places of musculoskeletal sensitivity (also called tender points), decreased muscle strength, chronic fatigue syndrome, and psychological adversities such as sleep disorders, anxiety, and depression [5,6]. FM is considered a multifactorial health condition, that is, its symptoms worsen or are maintained based on the interaction of several biological, psychological, and social factors [7].…”
Section: Introductionmentioning
confidence: 99%
“…To develop this study, we considered a mixed methods approach, considering that this is the type of approach recommended for health investigations, using information technologies such as tele-health and those reported in a study that, using an exploratory, sequential design, showed the importance of generating technology focused on the needs and requirements of users, in order to give support to people in the process of self-care and generate a positive impact on their health conditions (29) .…”
Section: Discussionmentioning
confidence: 99%
“…However, carrying out education interventions in medical consultation is, in most cases, nonviable, given the evident time restraints that accompany health care practice (Baird et al, 2016; Irving et al, 2017). Web‐based education interventions could be useful tools for educating patients without consuming time during consultations (Climent‐Sanz, Gea‐Sánchez, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%